The culture code the secrets of highly successful groups - Daniel Coyle (New York Bantam Books, 2018)
"From the New York Times bestselling author of The Talent Code comes a book that unlocks the secrets of highly successful groups and provides tomorrow's leaders with the tools to build a cohesive, motivated culture. Where does great culture come from? How do you build and sustain it in your group, or strengthen a culture that needs fixing? In The Culture Code, Daniel Coyle goes inside some of the world's most successful organizations--including Pixar, the San Antonio Spurs, and U.S. Navy'sSEAL Team Six--and reveals what makes them tick. He demystifies the culture-building process by identifying three key skills that generate cohesion and cooperation, and explains how diverse groups learn to function with a single mind. Drawing on examples that range from Internet retailer Zappos to the comedy troupe Upright Citizens Brigade to a daring gang of jewel thieves, Coyle offers specific strategies that trigger learning, spark collaboration, build trust, and drive positive change. Coyle unearths helpful stories of failure that illustrate what not to do, troubleshoots common pitfalls, and shares advice about reforming a toxic culture. Combining leading-edge science, on-the-ground insights from world-class leaders, and practical ideas for action, The Culture Code offers a roadmap for creating an environment where innovation flourishes, problems get solved, and expectations are exceeded. Culture is not something you are--it's something you do. The Culture Code puts the power in your hands. No matter the size of the group or the goal, this book can teach you the principles of cultural chemistry that transform individuals into teams that can accomplish amazing things together. Advance praise for The Culture Code "If you want to understand how successful groups work--the signals they transmit, the language they speak, the cues that foster creativity--you won't find a more essential guide than The Culture Code. This is a marvel of insight and practicality."--Charles Duhigg, New York Times bestselling author of The Power of Habit and Smarter Faster Better "I've been waiting years for someone to write this book--I've built it up in my mind into something extraordinary. But it is even better than I imagined.Daniel Coyle has produced a truly brilliant, mesmerizing read that demystifies the magic of great groups. It blows all other books on culture right out of the water. Read it immediately."--Adam Grant, New York Times bestselling author of Option B, Originals, and Give and Take"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Teams in the workplace